Confirmation of SLC5A7‐related distal hereditary motor neuropathy 7 in a family outside Wales. Issue 2 (21st May 2018) - Hamanaka, K.; Takahashi, K.; Miyatake, S.; Mitsuhashi, S.; Hamanoue, H.; Miyaji, Y.; Fukai, R.; Doi, H.; Fujita, A.; Imagawa, E.; Iwama, K.; Nakashima, M.; et al.
Abstract :